2015
DOI: 10.3141/2522-06
|View full text |Cite
|
Sign up to set email alerts
|

Live Load Distribution Factor at the Piers of Skewed Continuous Multicell Box Girder Bridges Subjected to Moving Loads

Abstract: The multicell box girder bridge is a popular choice of designers because of its large torsional stiffness. The skewness at the support line of bridges has a significant influence on distribution of live loads. The current American bridge design code, AASHTO load and resistance factor design (LRFD), defines several correction factor expressions to account for the skew effect in bridges. In addition, the effect of skewness on reactions of continuous multicell box girder bridges is obtained by using the skew corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(17 reference statements)
0
1
0
1
Order By: Relevance
“…Mohseni ve ark. [18], hareketli yüklere maruz eğrisel sürekli çok hücreli kutu kirişli köprülerin orta ayaklarında hareketli yük dağıtma katsayılarının etkisini incelemişlerdir. Yan ve ark.…”
Section: Introductionunclassified
“…Mohseni ve ark. [18], hareketli yüklere maruz eğrisel sürekli çok hücreli kutu kirişli köprülerin orta ayaklarında hareketli yük dağıtma katsayılarının etkisini incelemişlerdir. Yan ve ark.…”
Section: Introductionunclassified
“…The validity of the equations provided in AASHTO LRFD [13] was experimentally verified for a specified range of applicability. Mohseni et al [23] pointed out that the LDFs for shear and reaction at the piers and abutments of skewed bridges are different. It was, therefore, revealed that current AASHTO LRFD [13] LDF equations result in highly conservative values (by up to 25% for bridge with skew angle of 45 0 ) for the obtuse corners but un-conservative values (approximately 19%) for the acute corners of skewed superstructures.…”
Section: Introductionmentioning
confidence: 99%